5-Azacytidine inhibits proliferation and induces apoptosis of mouse bone marrow-derived mesenchymal stem cells. (11th October 2013) - Zhang, Fenxi; Wu, Junfang; Lu, Ming; Wang, Huaibin; Feng, Huigen
Abstract: In this study, we investigated the effect of 5-azacytidine on proliferation and apoptosis of bmMSCs. After exposure to different concentrations of 5-azacytindine, bmMSC proliferation and apoptosis were measured by MTT assay, Caspase-3 staining and western blotting. Our results show that 1 μM 5-azacytidine has no significant effect on viability of bmMSCs; however, 5–20 μM 5-azacytindine significantly inhibits bmMSC proliferation and expression of phospho-Akt; 10 and 20 μM 5-azacytidine markedly increases bmMSC apoptosis and expression of Caspase-3, Annexin V and Bax, and decreases expression of Bcl2. Our findings indicate that 5-azacytidine at the commonly used doses has toxicity to bmMSCs.